Oral rehabilitation using immediate implant placement in mandibular lateral incisors – a case report - Nila Sari; Abil Kurdi; Bambang Agustono Satmoko Tumali; Muhammad Dimas Aditya Ari (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: Dental problems often lead to missing teeth. After tooth extraction, the alveolar bone will undergo a healing phase, and this will cause some vertical and horizontal resorption. Immediate implant placement can shorten treatment time and preserve the rest of the alveolar bone. Purpose: The purpose of this study is to present a case of oral function, equilibrium and aesthetic rehabilitation using immediate implant placement. Case: A male patient aged 31 came to Dental Hospital Universitas Airlangga with a fractured anterior tooth. The tooth had fractured two weeks before he came to the hospital, and he wanted to improve his appearance. Case management: The mandibular incisor was fractured, and its residual root remained. The treatment plan was to undertake an immediate implant placement. The type of implant chosen was a bone level tapered implant SC roxolid® SLA Ø 2.9 mm and 10 mm long. Surgery was performed in two stages. The first stage was to extract the residual root, position the implant and apply the bone graft. The second stage was to position the healing abutment. A crown impression was made using the closed tray technique. The crown was cemented to the abutment. Conclusion: Immediate implant placement is an aesthetic means of rehabilitating a missing tooth, such as an anterior mandibular tooth.